Nutritional compositions of various potato noodles: Comparative analysis - Fen, Xu; Honghai, Hu; Xiaofeng, Dai; Qiannan, Liu; Yanjie, Huang; Hong, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
In this study, three kinds of noodles, wheat, Shepody potato and Atlantic potato noodles, were produced with blended powder consisting of wheat flour and certain amounts of various potato flours. In order to investigate the effects of potato flour on the nutritional characteristics of noodles, the nutrient compositions of four types of noodles were analyzed: fresh noodle, dried noodle, fresh noodle after boiling, and dried noodle after boiling. Results showed that the contents of protein, crude fiber, total ash, reducing sugar, vitamin B1, vitamin B2, vitamin B3, vitamin C, most mineral elements, dietary fiber, and amino acids in potato noodles were higher than those in wheat noodles. Furthermore, drying and boiling could decrease the contents of vitamin B1, vitamin B3, and mineral elements in noodles, but the nutrient contents in potato noodles remained higher than those in wheat noodles. The comprehensive nutritional values of noodles were evaluated using the index of nutritional quality, the results showed that the nutritional value of Shepody potato noodles was the highest, followed by that of Atlantic potato noodles and then wheat noodles. Keywords: potato, noodles; nutritional composition, nutritional value DOI: 10.3965/j.ijabe.20171001.2287 Citation: Xu F, Hu H H, Dai X F, Liu Q N, Huang Y J, Zhang H. Nutritional compositions of various potato noodles: Comparative analysis. Int J Agric & Biol Eng, 2017; 10(1): 218–225.